2017
DOI: 10.1088/1755-1315/67/1/012025
|View full text |Cite
|
Sign up to set email alerts
|

Daylight strategies for architectural studio facilities: the literature review

Abstract: Abstract. The implementation of daylighting strategies in buildings is a common aspect in architecture. However, due to the availability of inexpensive electricity, natural lighting strategies became insignificant, and been overlooked by designers. With the current concern over rapid increment on electricity cost, many designers now try to revitalized daylighting strategies in buildings. This includes educational buildings. In Malaysian cases, it is a norm that universities; especially during lecture and studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…The light source depends on the construction of the light source and the construction of the armature used, based on the distribution of light by the light source and the armature used in the lighting installation, which includes all electrical installations used to provide electric power to lamps and other electrical equipment, while the purpose of the lighting installation is to provide comfort to the eyes in carrying out tasks or jobs. Every lighting for each type of building is different, industrial lighting is certainly different from the lighting system in a house or building, to determine the required number of lights in a room it can be calculated [4], [5], [7], [8], [16], using the method the room utilization factor in the lighting model (N) and the formula is as follows:…”
Section: Building Physics For Lighting Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…The light source depends on the construction of the light source and the construction of the armature used, based on the distribution of light by the light source and the armature used in the lighting installation, which includes all electrical installations used to provide electric power to lamps and other electrical equipment, while the purpose of the lighting installation is to provide comfort to the eyes in carrying out tasks or jobs. Every lighting for each type of building is different, industrial lighting is certainly different from the lighting system in a house or building, to determine the required number of lights in a room it can be calculated [4], [5], [7], [8], [16], using the method the room utilization factor in the lighting model (N) and the formula is as follows:…”
Section: Building Physics For Lighting Modelsmentioning
confidence: 99%
“…Light intensity in lighting is an important aspect of a room, this arises because various problems will arise when the quality of the lighting intensity in the room lighting does not meet the standard elements that need to be applied [4]. Planning light in the lighting of a room must consider several factors, including the intensity of lighting when used for work, the intensity of lighting space in general, installation costs, energy consumption costs and maintenance costs [5], [6]. light in room lighting has an effect on eye health, even further bias on work safety and work productivity.…”
Section: Introductionmentioning
confidence: 99%
“…The study results indicated that the characteristics of façade patterns impacted the perceived spatial ambiance. A study by Muhammad Anas Bin Othman, Nur Azfahani Ahmad, and Azizah Md Ajis [5] investigated daylighting strategies for educational studios in universities through the maximization of daylighting penetration in the building space to create a more green-conducive studio. Another local study by Raghda M. ElBatran, and Walaa S.E.…”
Section: Introductionmentioning
confidence: 99%
“…This is not always possible since the objectives are conflicting with each other. For this reason, novel design techniques such as multi-objective optimization are currently being developed, aimed at window components [4,5]. Light shelves (LSs) are passive solutions for improving daylight penetration, reducing the related lights' electricity demand, and controlling windows' thermal aspects [6].…”
Section: Introductionmentioning
confidence: 99%